Impact of dissociation on the effectiveness of psychotherapy for post-traumatic stress disorder: meta-analysis - C. M. Hoeboer; R. A. De Kleine; M. L. Molendijk; M. Schoorl; D. A. C. Oprel; J. Mouthaan; W. Van der Does; A. Van Minnen (BJPsych Open, 2020)
BackgroundMany patients with post-traumatic stress disorder (PTSD) experience dissociative symptoms. The question of whether these dissociative symptoms negatively influence the effectiveness of psychotherapy for PTSD is unresolved.AimsTo determine the influence of dissociative symptoms on psychotherapy outcome in PTSD.MethodWe conducted a systematic search in Cochrane, Embase, PILOTS, PsycINFO, PubMed and Web of Science for relevant clinical trials. A random-effects meta-analysis examined the impact of dissociation on psychotherapy outcome in PTSD (pre-registered at Prospero CRD42018086575).ResultsTwenty-one trials (of which nine were randomised controlled trials) with 1714 patients were included. Pre-treatment dissociation was not related to treatment effectiveness in patients with PTSD (Pearson's correlation coefficient 0.04, 95% CI −0.04 to 0.13). Between-study heterogeneity was high but was not explained by moderators such as trauma focus of the psychotherapy or risk of bias score. There was no indication for publication bias.ConclusionsWe found no evidence that dissociation moderates the effectiveness of psychotherapy for PTSD. The quality of some of the included studies was relatively low, emphasising the need for high-quality clinical trials in patients with PTSD. The results suggest that pre-treatment dissociation does not determine psychotherapy outcome in PTSD.